READING CORNER SEBAGAI INTERVENSI PEDAGOGIS: IMPLEMENTASI, INTEGRASI DALAM MODEL PEMBELAJARAN, DAN DAMPAKNYA TERHADAP MINAT BACA SISWA - Sahra, As-sahra; Rustan, Edhy; Aswar, Nurul (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to describe the existence of a reading corner in a third-grade classroom at SD Negeri 1 Lalebbata, analyze its impact on students’ reading interest, and develop a reading instruction model integrated with field findings. The research employed a descriptive qualitative approach with a case study design. The subjects included the principal, teachers, and third-grade students, while data were collected through observation, interviews, and documentation. Data were analyzed using data reduction, data display, and conclusion drawing based on the Miles and Huberman model. The results showed that the reading corner demonstrated a strong presence through aspects such as location, facilities, variety of reading materials, arrangement, rules, reading schedules, and story-sharing activities. These aspects were consistently utilized by students. Furthermore, the use of the reading corner had a positive impact on increasing students’ reading interest, reflected in four main indicators: enjoyment, curiosity, information needs, and intrinsic motivation. Based on these findings, a reading instruction model called the Read–Feel–Share Cycle (RFSC Model) was developed. This model consists of five stages and integrates both physical and emotional experiences in reading activities. It is recommended as an applicable and contextual approach to strengthen literacy culture in elementary schools.